Evidence-Based Nutritional Interventions for Sarcopenia: A Systematic Review of Randomized Controlled Trials - Putu Prabhawati Dwikrisna; Ni Made DwiAsti Lestari (Jurnal EduHealth, 2026)
Background: Sarcopenia is a progressive condition characterized by decreased skeletal muscle mass, strength, and function, which impacts the quality of life of the elderly. Nutritional intervention is one potential approach in sarcopenia management, but its effectiveness still shows variable results. Objective: To assess the effectiveness of various nutritional interventions on muscle mass, muscle strength, and physical function in individuals with sarcopenia or at risk of developing it. Methods: A systematic review was conducted according to the PRISMA 2020 guidelines. A comprehensive literature search was conducted through PubMed/MEDLINE, Science Direct, and Google Scholar databases from inception to January 2025. Inclusion criteria included randomized controlled trials (RCTs), quasi-experimental, or cohort studies evaluating nutritional interventions in populations ≥50 years with sarcopenia. Risk of bias was assessed using Cochrane RoB 2 and ROBINS-I. Analysis was conducted narratively and stratified by intervention type. Results: A total of 15 studies with a total of 4,319 participants met the inclusion criteria. The majority of studies (73.3%) used a double-blind RCT design, with intervention durations ranging from 8 weeks to 3 years. Supplementation with leucine-enriched protein and vitamin D consistently significantly increased appendicular lean mass (0.17 kg; P=0.045). Omega-3 fatty acids were shown to be effective in increasing skeletal muscle mass, muscle strength, and vastus lateralis thickness by up to 3.5%. The combination of nutrition and exercise provided the most optimal results, with significant improvements in grip strength, muscle mass, and physical function. Most interventions were well tolerated without serious side effects. Conclusion: Nutritional interventions, particularly protein with leucine, vitamin D, and omega-3, effectively improved sarcopenia parameters. A combined approach with exercise provided the best results in sarcopenia management.